A Rural High School's Collaborative Approach to School Improvement - Patti L. Chance; Susan N. Segura (Journal of Research in Rural Education, 2009)
This study examines the events and behaviors associated with the improved and sustained student achievement in a rural high school. The rural high school highlighted in this study showed significant improvement and sustained achievement over a three year period as defined in the following areas: (a) test scores, (b) achievement of Adequate Yearly Progress, and (c) attendance and graduation rate. This case study identified various factors associated with the change process, including leadership behaviors, organizational structure, and particular characteristics of the school within its rural context. Qualitative analyses suggest that both organizational practices and instructional leadership behaviors contributed to developing successful collaborative efforts that, in turn, led to improved student achievement. Three essential elements identified for successful collaboration were (a) scheduled time for teacher collaboration; (b) structured and focused collaboration time devoted to improving instruction and student achievement, and; (c) leadership behaviors that focused on student-centered planning and accountability. Relationship and contextual factors associated with rural schools and small communities were identified as advantageous to developing a collaborative process for school improvement.